2012
DOI: 10.1007/s10637-012-9852-4
|View full text |Cite
|
Sign up to set email alerts
|

The vascular disrupting agent ombrabulin (AVE8062) enhances the efficacy of standard therapies in head and neck squamous cell carcinoma xenograft models

Abstract: Targeting tumor vasculature is an emerging strategy in cancer treatment. Promising results have been shown in preclinical studies when vascular disrupting agents (VDAs) are used in combination with other anticancer therapies. Because radiation therapy with concurrent cisplatin or cetuximab has become standard treatment for patients with locally advanced head and neck squamous cell carcinoma (HNSCC), we investigated whether the VDA ombrabulin (AVE8062) could improve the antitumor activity of radiation plus cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Ombrabulin enhances the efficacy of standard therapies (radiation plus cisplatin and radiation plus cetuximab) in head and neck squamous cell carcinoma (HNSCC) xenograft models. A specific action of ombrabulin towards intratumoral vessels rather than to the peritumoral vasculature was demonstrated by means of immunochemical staining of HNSCC tumors [92]. The design of CA-4 analogs as VDAs was the subject of a concise review by Rajak et al, who paid special attention to cis-restricted isomers [93].…”
Section: Tubulin-binding Stilbenes As Vdasmentioning
confidence: 99%
“…Ombrabulin enhances the efficacy of standard therapies (radiation plus cisplatin and radiation plus cetuximab) in head and neck squamous cell carcinoma (HNSCC) xenograft models. A specific action of ombrabulin towards intratumoral vessels rather than to the peritumoral vasculature was demonstrated by means of immunochemical staining of HNSCC tumors [92]. The design of CA-4 analogs as VDAs was the subject of a concise review by Rajak et al, who paid special attention to cis-restricted isomers [93].…”
Section: Tubulin-binding Stilbenes As Vdasmentioning
confidence: 99%
“…Synergistic effects [76] KML001 Irinotecan Colon carcinoma Preclinical Increased antitumor activity [83] Ombrabulin (AVE8062) Irradiation + cisplatin or cetuximab HNSCC Preclinical Increased tumor growth delay [88] ASA404 Taxanes Glioblastoma Preclinical Synergistic effect [77] ASA404 Everolimus Renal cell carcinoma Preclinical Extensive necrosis and reduction in the viable rim [79] ASA404 Photodynamic therapy Colon adenocarcinoma tumors Preclinical Potentiated antitumor activity [80] ASA404 Taxanes Advanced prostate cancer Clinical (Phase II) Activity with acceptable toxicity [32] ASA404 Carboplatin and paclitaxel NSCLC at stage III or IV Clinical (Phase III) Failed [33] Plinabulin (NPI-2358)…”
Section: Cisplatin Colon Adenocarcinoma Preclinicalmentioning
confidence: 99%
“…AVE8062, associated to irradiation and either cisplatin or cetuximab, increased tumor growth delay in experimental tumor models [88].…”
Section: Docetaxelmentioning
confidence: 99%
“…A recent mouse model of head and neck squamous cell carcinoma demonstrated that ombrabulin treatment augmented the anti-tumour effectiveness of the standard treatment regimen of radiation and cisplatin or cetuximab [ 101 ]. Ombrabulin is in phase III trials for the treatment of soft tissue sarcoma, in phase II trials in combination with taxane and platinum drugs (docetaxel and cisplatin or paclitaxel and carboplatin) for the treatment of patients with metastatic non-small cell lung cancer (NSCLC) and in a number of phase I trials in combination with other drugs in solid tumours.…”
Section: Combretastatin Derivatives (Oxi 4503 Ombrabulin)mentioning
confidence: 99%